Reinventing leadership: new approaches and the perspective of Italian millennials. (14th August 2019) - D'Amato, Vittorio; Macchi, Francesca
The business world is changing and it is expected that a new generation of employees (millennials), whose needs, ideas and expectations are different from those of the past, will make up 75% of the workforce by 2025. The present study is aimed at understanding what competencies are needed for a leader to relate to millennials. To answer this question, the authors have collected the perspective of this group from the millennials themselves. Our proposal is based on a wealth of experience and integrates many of the latest, best, most robust and practical approaches on the theme of leadership, with research carried out on a group of 240 freshmen in our university in order to obtain the millennial point of view.